Stephen Daldry’s The Reader in Chekhov’s Mirror - Reichmann, Angelika (Hungarian Journal of English and American Studies, 2021)
This essay is devoted to a discussion of Stephen Daldry and David Hare’s film adaptation of Bernhard Schlink’s critically acclaimed but controversial Holocaust novel, The Reader (1995; 2008), through one of the film’s many intertexts—Anton Chekhov’s “The Lady with the Little Dog” (1899). The scenes related to this short story are crucial to the understanding of Daldry and Hare’s filmic reinterpretation of Schlink’s novel, since they form the mise en abyme of Hanna and Michael’s ambiguous story and stalled self-reflection. The parallels and contrasts of Chekhov’s and the filmmakers’ narratives call viewers’ attention to the ambivalences inherent in the main characters’ representation. Inspired by a passing reference to Chekhov in Schlink’s novel, the scenes alluding to “The Lady with the Little Dog” provide a metanarrative in The Reader, and, as such, reflect the adaptors’ heightened sensitivity to the ambivalences and complexities of reflecting the trauma of the Holocaust—not only for “the second generation” of Germans after World War II.  (AR)